2019
DOI: 10.1108/rpj-04-2018-0091
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of 3D printed sand moulds using micro-focus X-ray computed tomography

Abstract: Purpose Micro-focus X-ray computed tomography (CT) can be used to quantitatively evaluate the packing density, pore connectivity and provide the basis for specimen derived simulations of gas permeability of sand mould. This non-destructive experiment or following simulations can be done on any section of any size sand mould just before casting to validate the required properties. This paper aims to describe the challenges of this method and use it to simulate the gas permeability of 3D printed sand moulds for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 5 publications
1
14
0
Order By: Relevance
“…(Kadauw, 2014) characterized the local density of sand mold using industrial computed tomography, and found good agreement with the experimental density of sand mold. Some typical results were reported recently by (Sivarupan et al, 2018) for the use of X-ray µ-CT to characterize the additively processed porous structure like 3DP sand mold. (Anbar et al, 2019) used LBM to predict permeability from a computer-generated sphere packing, and to study the impact of sand compaction from the simulations.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…(Kadauw, 2014) characterized the local density of sand mold using industrial computed tomography, and found good agreement with the experimental density of sand mold. Some typical results were reported recently by (Sivarupan et al, 2018) for the use of X-ray µ-CT to characterize the additively processed porous structure like 3DP sand mold. (Anbar et al, 2019) used LBM to predict permeability from a computer-generated sphere packing, and to study the impact of sand compaction from the simulations.…”
Section: Introductionmentioning
confidence: 86%
“…An average pore connectivity value of Z ≈ 3 is obtained. In this regard, (Sivarupan et al, 2018) showed in a previous work that the speed at which the recoater spreads the sand particles on the job box platform affects the poreconnectivity, hence affecting the permeability. It can be deduced from the results displayed in Table 2 that the size of the grain does not affect pore connectivity, in contrast to the case of recoating speed.…”
Section: Grain Size Distribution and Measurement Of Tortuositymentioning
confidence: 95%
“…Microfocus X-ray computed tomography can be used to quantitatively evaluate the packing density, pore connectivity and provide the basis for specimen-derived simulations of gas permeability of sand mold. Sivarupan et al (2019) simulated the gas permeability of 3D printed sand molds with this method.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to all AM processes, 3DSP requires a three-dimensional digital model of the desired part, which may be created directly with a computer-aided drafting software package and/or reverse-engineered from a three-dimensional point cloud of the desired final part geometry (Campbell et al , 2011). Simultaneously, this three-dimensional model can be used in simulation analysis for examination of metal flow and solidification rates for a range of casting and mold designs across different alloy systems (Sivarupan et al , 2019; Sama et al , 2018). Once this model is exported as a stereolithography file, process planning for every slice across the part in a layer-by-layer technique can be completed (Campbell et al , 2011; Druschitz et al , 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Unlike traditional sand or high-pressure die casting, 3DSP castings and mold design are not limited by the need for draft angles, minimum wall thickness (based on 3DSP capabilities), aspect ratio, rounding of angular features and parting lines with their associated flashing (Sivarupan et al , 2019; Sama et al , 2018). Complex internal features (e.g.…”
Section: Introductionmentioning
confidence: 99%